Climate neutrality of the French energy system: overview and impacts of sustainable aviation fuel production - Merceron, Louis; Boissonnet, Guillaume; Maréchal, François (Frontiers in Energy Research, 2024)
CO2 emission reduction of sectors such as aviation, maritime shipping, road haulage and chemicals production is challenging, but necessary. Although these sectors will most likely continue to rely on carbonaceous energy carriers, they are expected to gradually shift away from fossil fuels. In order to do so the prominent option is to utilize alternative carbon sources-like biomass and CO2 originating from carbon capture-for the production of non-fossil carbonaceous vectors (biofuels and e-fuels). However, the limited availability of biomass and the varying nature of other carbon sources, necessitate a comprehensive evaluation of trade-offs between potential carbon uses and existing sources. Then it is primordial to understand the origin of carbon used in Sustainable Aviation Fuel (SAF) to understand the implications of defossilizing aviation for the energy system. Moreover, the production of SAF implies deep changes to the energy system that are quantified in this work. This study utilises the linear programming cost optimisation tool Energyscope TD, to analyse the holistic French energy system, encompassing transport, industry, electricity, and heat sectors while ensuring net greenhouse gas neutrality. A novel method to model and quantify carbon flows within the system is introduced, enabling a comprehensive assessment of greenhouse gases neutrality. This study highlights the significance of fulfilling clean energy requirements and implementing carbon dioxide removal measures as crucial steps toward achieving climate neutrality. Indeed, to reach climate neutrality a production of 1046 TWh of electricity by non-fossil sources is needed. Furthermore, the findings underscore the critical role of efficient carbon and energy valorisation from biomass giving evidence that producing fuels by combining biomass and hydrogen is optimal. The study also offers valuable insights into the future cost and impact of SAF production for air travel originating from France. Namely, the European law ReFuel-EU would increase the price of plane tickets by +33% and would require 126 TWh of hydrogen and 50 TWh of biomass to produce the necessary 91 TWh of jet fuel. Finally, a discussion on the implications of the assumption behind the production of SAF is performed.